The Role of TNF-Alpha in the Wound Healing Process: Molecular and Clinical Perspectives - A Systematic Literature Review - Yusuf, Khaidir (RSUP Dr Moh Hoesin Palembang, 2022)
Wounds are conditions of damage and partial loss of body tissue caused by physical trauma, sharp objects, blunt objects, temperature fluctuations, chemical exposure. Wound healing is a complex interaction between cells, cytokines, mediators, and blood vessels as a natural physiological response to tissue damage. TNF-α has a crucial role in the wound healing process, facilitating body immunity, immune cell mobilization, fibroblast cell proliferation, keratinocytes, and growth factor expression. Although TNF-alpha has benefits in the early stages of wound healing, excessively high levels or a sustained inflammatory response can lead to problems, such as excessive scar tissue formation or blockages, which can impede the wound healing process. This study utilized the PRISMA-ScR (Scoping Review) protocol. A review was conducted of articles discussing the Role of TNF-Alpha in the Wound Healing Process: Molecular and Clinical Perspectives within the last 10 years. Literature search in this study using PubMed, ScienceDirect, Elsivier and Google Scolar databases Search using English, abstract and full text. After searching with the keywords: The Role of TNF-Alpha, 19,022 articles were found. The search continued using the keyword The Role of TNF-Alpha in the Wound Healing found 346 articles. The last search using the keyword The Role of TNF-Alpha in the Wound Healing: Molecular and Clinical found 26 articles. TNF-α plays an important role in the early stages of cutaneous wound healing, significantly delayed after day 3, but not by day 7. TNF-α has a crucial role in the early stages of skin wound healing, and its administration is recognized to have a positive impact on the healing response, which may pave the way for innovative strategies to address chronic skin wound healing problems.